Uncanny Reversals: Paul Celan's CounterPoetics. Issue 1 (April 2017) - Balzan, Janice Sant
Abstract : This article presents a reading of Paul Celan's Der Meridian speech that draws attention to its countertextual impulse. Celan's most sustained reflection on poetry begins by making a distinction between art, which he describes as 'uncanny', and poetry, which has the power to bear witness to the 'presence of the human'. The development of Der Meridian, however, reveals that this stark distinction is untenable. Celan will go on to show that art and poetry are more intricately related than he first suggests. Whilst the uncanniness of art estranges and forgets the human, it also provides the necessary position from which to turn toward the human. Hence Celan's claim that poetry must tread the route of art if it is to bear witness to the human. This article locates the countertextual in the encounter between poetry and art, and argues that Celan's exploration of the 'uncanny' is central to his reflections on poetry.